Effects of the mandibular protraction appliance FLF on the face: morphometric analysis (Research, Society and Development, 2022)
Objective: To determines the effects of the Mandibular Protraction Appliance FLF associated with fixed orthodontic braces on the face, by means of morphometric analysis. Method: the sample consisted of 60 photographs taken in profile view (30 initial and 30 final photographs) of 30 young Brazilians (17 males and 13 females), with a mean initial age of 12 years and 7 months. Patients who participated in this sample, used the FLF device, and had to have white skin color, with Class II malocclusion, 1st division (minimum ½ class II), mandibular deficiency and convex profile, complete permanent dentition, and balanced growth pattern. The mean time of use of the FLF was 8 months and the mean total time of treatment with fixed devices and MPA FLF was 2 years and 1 month. For comparison between the FLF sample and the skeletal pattern according to Farkas, and comparison between the Pre- and Post-phases, the paired “t” test was used. The significance level of 5% (p